Peningkatan Pemasaran pada UMKM di Kelurahan Salamsari Kecamatan Boja Kabupaten Kendal - Teti Susilowati; Muryanto Agus Nuswantoro; Emy Susiatin (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2025)
This service aims to increase understanding of good business management among MSMEs in Salamsari Village, Boja District, Kendal Regency, especially in the field of marketing/promotion. Salamsari Village is a highland area with the majority of residents working as farm laborers and traders. Business actors, especially women, manage various processed food products such as criping, peyek, kembang goyang, savory cendol, widaran, tempeh chips, lumpit and sticky rice tape. However, marketing their products is still limited to a local scale and has not utilized digital media optimally. Apart from that, attention to packaging design is still minimal.Service activities include socializing marketing strategies in the digital era, such as the use of social media, online marketplaces, and attractive packaging designs. Before this activity, business actors did not fully understand the benefits of good marketing in increasing sales turnover, expanding market share and developing business. The service team provides education about online marketing that is cost-effective and effective in expanding market reach. As a result, MSME players showed high enthusiasm and realized the importance of appropriate marketing strategies, both offline and online, to support the sustainability of their businesses.This activity is expected to be able to encourage MSME players to increase their competitiveness, expand markets and increase turnover through the use of digital technology. The output of this service includes publications in accredited national journals, recording Intellectual Property Rights (IPR), and disseminating information through mass media.